Thermal Analysis of a Forced Flow Diffusion Absorption Refrigeration System for Fishing-Boat Exhaust Waste Heat Utilization - Du, Shuai (Frontiers in Energy Research, 2021)
Ammonia water absorption refrigeration systems are effective to utilize fishing-boat exhaust waste heat for frozen preservation. However, the liquid level control and the use of the solution pump characterized as small flowrate and high pressure head result in poor robustness and reliability of the traditional system. Besides, the system is necessary to be designed anti-swaying and anti-corrosion. This paper proposes a forced flow diffusion absorption refrigeration system, in which a canned motor pump and an ejector are employed to provide the driving forces of the gas and liquid loops. The near single pressure operation allows for a simple passive liquid level control without throttling valve regulations. The system adopts an integrated cooling strategy which allows the system to operate under swaying conditions, and the external seawater cooled heat exchanger avoids the internal corrosion and leakage. The thermal analysis shows the system is valid to be operated under wide operating conditions, and the coupled gas and solution circulation ratios determined the performance of the novel system. There is an optimal ammonia mass fraction difference in the gas loop to obtain the optimal COP. The COP reaches 0.4 when the temperatures at the outlets of generator, evaporator, absorber and condenser are 160oC, -15oC, 35oC and 35oC, respectively. The novel system provides a reliable absorption refrigeration system design for fishing-boat applications.